1997
DOI: 10.1007/bf00941807
|View full text |Cite
|
Sign up to set email alerts
|

Successful combined resection of carcinoma of the esophagus and adrenal metastasis: Report of a case

Abstract: We report herein the case of a 56-year-old man who underwent successful combined resection of carcinoma of the esophagus and an adrenal metastasis. The patient presented with carcinoma of the thoracic esophagus, and an adrenal tumor was incidentally detected by computed tomography(CT). Complete removal of the carcinoma was accomplished along with a combined resection of the thoracic esophagus and left adrenal gland. Surgery was followed by the administration of anticancer chemotherapeutic agents. He is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Single adrenal metastasis is very rare, and only a few cases with resection have been reported to survive over a year. [3][4][5][6] In our case, we resected a solitary adrenal metastatic tumor. Our patient's quality of life has been good for 42 months.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single adrenal metastasis is very rare, and only a few cases with resection have been reported to survive over a year. [3][4][5][6] In our case, we resected a solitary adrenal metastatic tumor. Our patient's quality of life has been good for 42 months.…”
Section: Resultsmentioning
confidence: 99%
“…2 In addition, metastasis to distant organs is frequent, particularly into the liver, lungs, and adrenal glands, which have been rarely operated upon. [3][4][5][6]11,12 However, we report here a case of resection of solitary adrenal metastasis from esophageal carcinoma following esophagectomy with no recurrence.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Multimodality therapy – consisting of chemotherapy, radiotherapy, and surgery – has been well established as an effective treatment for primary locally advanced esophageal carcinoma 1,2,9–11 . Although several studies have reported using multimodality therapy for far advanced esophageal cancer, most series include few, if any, patients with distant organ metastases 12–15 . Therefore, the outcomes and prognosis in esophageal cancer patients with organ metastases who receive multimodality therapy remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[3] The prevalence of the neoplastic dissemination to the adrenal glands varies from about 5% in clinical evaluation studies to 13.6% in autopsies studies. [24] In this context, there are some isolated reports in the literature suggesting the benefit of adrenalectomy in patients with esophageal carcinoma, when the gland represents a single metastatic site, suggesting some benefits in the survival rates of these individuals. [345]…”
mentioning
confidence: 99%